Long-Term Effects of Bevacizumab on Vestibular Schwannoma Volume in Neurofibromatosis Type 2 Patients - Killeen, Daniel E.; Klesse, Laura; Tolisano, Anthony M.; Hunter, Jacob B.; Kutz, Joe Walter, Jr (Journal of Neurological Surgery Part B: Skull Base, 2019)
Introduction Bevacizumab offers a medical treatment that may slow the growth of vestibular schwannomas (VS) and possibly preserve hearing in patients with neurofibromatosis type 2 (NF2). This study aims to investigate the effect of long-term bevacizumab treatment on VS progression.Methods Demographic, clinical, audiometric, and radiographic data were collected from the medical records of NF2 patients treated with bevacizumab at a tertiary medical center.Results Eleven tumors from seven NF2 patients treated with bevacizumab were analyzed. The median age was 17 years (range: 12–47 years). Median bevacizumab treatment time was 33 months (range: 12–74 months). Of five patients with serviceable hearing pretreatment, one (20%) maintained serviceable hearing during bevacizumab therapy. Significantly slower growth rates for both tumor diameters and tumor volumes were identified during active bevacizumab treatment. Median tumor diameters and volumes during active bevacizumab treatment were 0 cm/year (range: –0.13–0.17 cm/year) and 0.1 cm3/year (range: –0.92–0.41), compared with 0.37 cm/year (range: 0–1.5 cm/year, p = 0.0011) and 1.38 cm3/year (range: 0.013–3.74), respectively, without bevacizumab treatment (p = 0.0263). Reduced tumor progression was noted with bevacizumab treatment utilizing both linear greatest diameter (hazard ratio 0.16, p = 0.006) and segmentation volumes (hazard ratio 0.15, p = 0.023). Complications of bevacizumab treatment included fatigue (43%), nausea/vomiting (43%), hypertension (43%), epistaxis (29%), and proteinuria (29%). One subject had a cerebrovascular accident detected on screening magnetic resonance imaging without symptoms or neurological sequelae.Discussion Bevacizumab may reduce tumor growth rate and the risk of progression based on both volumetric and linear measurements.
Keywords: vestibular schwannoma; neurofibromatosis type 2; bevacizumab; Avastin; acoustic neuroma